Patient harm from cardiovascular medications. (July 2021) - Paradissis, Chariclia; Cottrell, Neil; Coombes, Ian; Scott, Ian; Wang, William; Barras, Michael
Background: Medication harm can lead to hospital admission, prolonged hospital stay and poor patient outcomes. Reducing medication harm is a priority for healthcare organisations worldwide. Recent Australian studies demonstrate cardiovascular (CV) medications are a leading cause of harm. However, they appear to receive less recognition as 'high risk' medications compared with those classified by the medication safety acronym, 'APINCH' (antimicrobials, potassium, insulin, narcotics, chemotherapeutics, heparin). Our aim was to determine the scale and type of medication harm caused by CV medications in healthcare. Methods: A narrative review of adult (>16 years) medication harm literature identified from PubMed and CINAHL databases was undertaken. Studies with the primary outcome of measuring the incidence of medication harm were included. Harm caused by CV medications was described and ranked against other medication classes at four key stages of a patient's healthcare journey. Where specified, the implicated medications and type of harm were investigated. Results: A total of 75 studies were identified, including seven systematic reviews and three meta-analyses, with most focussing on harm causing hospital admission. CV medications were responsible for approximately 20% of medication harm; however, this proportion increased to 50% in older populations. CV medications were consistently ranked in the top five medication categories causing harm and were often listed as the leading cause. Conclusion: CV medications are a leading cause of medication harm, particularly in older adults, and should be the focus of harm mitigation strategies. A practical approach to generate awareness among health professionals is to incorporate 'C' (for CV medications) into the 'APINCH' acronym. Plain language summary: Patient harm from cardiovascular medications: Background: Harm from medications can cause poor patient outcomes. Certain medications have been identified as 'high risk' and are known to cause high rates of harm. 'High risk' medications are included in medication guidelines used by health professionals. Cardiovascular medications (e.g. blood pressure and cholesterol medications) are important and have many benefits. Recent studies have found cardiovascular medications to cause high rates of harm. Cardiovascular medication harm is often under-recognised in clinical practice. Some guidelines do not consider cardiovascular medications to be 'high risk'. Method: This review investigated the extent of harm caused by cardiovascular medications in adults across four healthcare settings: (1) at the time of hospital admission; (2) during hospital admission; (3) after hospital; and (4) readmission to hospital. Harm caused by cardiovascular medications was ranked against other medication classes. We investigated the type of cardiovascular medications to cause harm and the type of harm caused. Results: Seventy-five studies were reviewed across 41 countries. Cardiovascular medications were ranked within the top five medications to cause harm. Cardiovascular medications were a leading cause of harm in each healthcare setting investigated. Harm caused by cardiovascular medications was common in older adults (>65 years). Cardiovascular medications often caused preventable harm. Medications to treat high blood pressure and abnormal heart rhythms were the most common causes of harm. We reported kidney injury, electrolyte changes and low blood pressure as common types of harm. Conclusion: Increased focus on cardiovascular medications in clinical practice is needed. Health professionals need to carefully prescribe and frequently review cardiovascular medications, especially in older adults. Patient and health professional discussions should be based on both the benefits and harms of cardiovascular medications. Cardiovascular medications should be included in all 'high risk' medication guidelines.